2005
DOI: 10.1590/s0103-97332005000100017
|View full text |Cite
|
Sign up to set email alerts
|

The Coester line in relativistic mean field nuclear matter

Abstract: The Walecka model contains essentially two parameters that are associated with the Lorentz scalar (S) and vector (V ) interactions. These parameters are related to a two-body interaction consisting of S and V , imposing the condition that the two-body binding energy is fixed. We have obtained a set of different values for the nuclear matter binding energies (BN ) at equilibrium densities (ρo). We investigated the existence of a linear correlation between B N and ρ o , claimed to be universal for nonrelativisti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Coester et al [22] observed that, in an energy versus density plot, the saturation points of nuclear matter obtained by employing different realistic potentials are located along a band (Coester band). Also, in a relativistic framework it was observed such strong correlation [24]. The displayed nuclear matter binding energy (B A /A ≡ B (A,0) /A) versus saturation density [ ρ o = (2/3)k 3 F /π 2 , with k F the Fermi momentum] results are within a narrow band [22].…”
mentioning
confidence: 78%
“…Coester et al [22] observed that, in an energy versus density plot, the saturation points of nuclear matter obtained by employing different realistic potentials are located along a band (Coester band). Also, in a relativistic framework it was observed such strong correlation [24]. The displayed nuclear matter binding energy (B A /A ≡ B (A,0) /A) versus saturation density [ ρ o = (2/3)k 3 F /π 2 , with k F the Fermi momentum] results are within a narrow band [22].…”
mentioning
confidence: 78%